2019
DOI: 10.1088/1361-6668/ab4d9e
|View full text |Cite
|
Sign up to set email alerts
|

Ta, Ti and Hf effects on Nb3Sn high-field performance: temperature-dependent dopant occupancy and failure of Kramer extrapolation

Abstract: The increasing demand for improving the high-field (16-22 T) performance of Nb3Sn conductors requires a better understanding of the properties of modern wires much closer to irreversibility field, HIrr. In this study we investigated the impact of Ta, Ti and Hf doping on the high-field pinning properties, the upper critical field, Hc2, and HIrr. We found that the pinning force curves of commercial Ti and Ta doped wires at different temperatures do not scale and that the Kramer extrapolation, typically used by m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
(69 reference statements)
1
10
0
Order By: Relevance
“…In fact, fitting these data shows that only a minor amount of Ta, ~ 12%, sits on the Sn site. Interestingly, this level of split site occupancy for Ta is compatible with that found for the Ta-doped RRP wire after similar heat-treatment 23 , suggesting that the presence of Hf does not affect the Ta occupancy behaviour. A similar analysis of the A15 layer for the Hf edge shows no clear indication of Hf being in the A15 structure (Fig.…”
Section: Resultssupporting
confidence: 83%
“…In fact, fitting these data shows that only a minor amount of Ta, ~ 12%, sits on the Sn site. Interestingly, this level of split site occupancy for Ta is compatible with that found for the Ta-doped RRP wire after similar heat-treatment 23 , suggesting that the presence of Hf does not affect the Ta occupancy behaviour. A similar analysis of the A15 layer for the Hf edge shows no clear indication of Hf being in the A15 structure (Fig.…”
Section: Resultssupporting
confidence: 83%
“…It is seen that the magnetic and transport J c, non-Cu values are more or less on the same level. However, the B irr (4.2 K) extracted from the magnetic J c -B curve is about 21.8 T, while that from the transport result is about 24 T. A previous highfield M-µ 0 H loop measurement at 4.2 K by Tarantini et al [28] reported a B irr (4.2 K) of ∼22 T for a similar RRP ® strand. That study also pointed out the discrepancy between magnetic and transport B irr values.…”
Section: Resultsmentioning
confidence: 78%
“…A study of the doping mechanism has indicated that the site displacement behavior in the Nb 3 Sn lattice differs between these elements. Extended x-ray absorption fine structure measurements revealed that Ti atoms are preferentially localized in Nb sites, whereas Ta atoms can sit in both Nb and Sn sites [19,20]. This phenomenon may account for the difference in the enhancement of B c2 when doping with these elements.…”
Section: Introductionmentioning
confidence: 94%